Consumers' awareness towards nutritional label in purchasing agricultural food products - Mohd Nawi, Nolila; Jumain, N. A. (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Nowadays, consumer already exposed towards the label that stated on the packaged of food they buy. The aim of food labelling is actually to provide consumers with information which may influence their purchasing decision. Thus, the aim of this paper is to determine consumers’ awareness towards nutritional label in purchasing agricultural food products. Primary data was collected using structured questionnaire with 400 respondents in Johor Bharu, Johor. Respondents was selected using simple random sampling method and survey were then undertaken through face-to-face interview. Data collected was then analyzed using descriptive analysis, chi square analysis and factor analysis. The results of the study revealed that majority of the respondents are aware about the nutritional label and read the label when purchased agricultural food products. Chi square analysis showed a significant association between socio-demographic profile such as income and residential location with respondent’s awareness towards nutritional label in purchasing agricultural food products. Furthermore, six factors were found influencing respondent’s awareness towards nutritional label including mass media, family influenced, social media, government, label design and friends influenced. The findings of this study can be used in assisting the relevant government agencies to come out with a better awareness campaign to the consumers on the important of nutritional label. For the food manufacturers, the findings can be used in developing a better marketing strategy for their products especially on the labeling of the food product.